Preparation of Cellulose Acetate Membranes via Phase Inversion for Osmometric Molecular Weight Determination of Macromolecules - Syarifatul Lailah; Indarti, Dwi; Piluharto, Bambang; Mulyono, Tri; dwi ananda, Tinok (Indonesian Chimica Letters, 2026)
Membrane osmometry is a crucial analytical technique for determining the molecular weight of macromolecules, demanding highly selective semi-permeable membranes to prevent solute leakage. This study investigates the effect of solvent evaporation time (1 to 5 minutes) during the phase inversion fabrication of cellulose acetate (CA) membranes on their physicochemical properties and semi-permeability. The synthesized membranes were evaluated for macroscopic appearance, density, swelling degree, and semi-permeability performance using dextran (100-200 kDa) as a model macromolecule. The results demonstrated that while the macroscopic structures remained uniform, prolonging the evaporation time significantly altered the microscopic morphology. Increasing the evaporation time to 5 minutes maximized the localized polymer concentration, resulting in the highest membrane density (1.55 g/mL) and the lowest swelling degree (17.62%). This highly compact structure provided a superior physical barrier, yielding the most optimal semi-permeability with minimal solute leakage. Furthermore, the application of this 5-minute optimized membrane in a membrane osmometer successfully determined the average molecular weight of dextran to be 122.45 kDa, which perfectly aligns with the theoretical range. The analytical measurement exhibited excellent reproducibility with a coefficient of variation (CV) of 1.8% and an accuracy of approximately 80%. These findings conclusively establish that controlling the evaporation time is a highly effective approach to tailoring the strict selectivity of CA membranes for precise osmometric applications.